2003
DOI: 10.1242/jcs.00420
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic insults impair Na+, K+-ATPase activity as a mechanism of neuronal death mediated by concurrent ATP deficiency and oxidant stress

Abstract: The Na+, K+-ATPase (Na+,K+-pump) plays critical roles in maintaining ion homeostasis. Blocking the Na+, K+-pump may lead to apoptosis. By contrast, whether an apoptotic insult may affect the Na+,K+-pump activity is largely undefined. In cultured cortical neurons, the Na+, K+-pump activity measured as a membrane current Ipump was time-dependently suppressed by apoptotic insults including serum deprivation, staurosporine, and C2-ceramide, concomitant with depletion of intracellular ATP and production of reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 66 publications
5
99
1
Order By: Relevance
“…29 Na þ ,K þ -ATPase is sensitive to ROS insult, thus has been repeatedly reported to lose its activity under oxidative stress. 17,[30][31][32] However, among a variety of biological events, generation of ROS is often useful and necessary for appropriate signal transduction. For instance, ROS were critically involved in p38 mitogen-activated protein kinase activation in angiotensin II-mediated vascular smooth muscle cell hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Na þ ,K þ -ATPase is sensitive to ROS insult, thus has been repeatedly reported to lose its activity under oxidative stress. 17,[30][31][32] However, among a variety of biological events, generation of ROS is often useful and necessary for appropriate signal transduction. For instance, ROS were critically involved in p38 mitogen-activated protein kinase activation in angiotensin II-mediated vascular smooth muscle cell hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…17 In brief, cells before or after treatment were collected and lysed, equal amounts of protein (500 mg) from supernatants were incubated overnight at 41C with 5 mg anti-phosphor-serine antibody (Cell signaling, Danvers, MA, USA). Antibody was subsequently bound to a saturating amount of protein A-Sepharose beads at 41C for 3-5 h. Centrifugation (5000 r.p.m.)…”
Section: Immunoprecipitation Protein Phosphorylation Assaymentioning
confidence: 99%
“…It also affects mitochondrial metabolism (55), with consequent inhibition of substrate oxidation, reduction in respiration, and decrease in the cellular ATP/ADP ratio. In this case, activation of Na,K-ATPase (the major energy consumer in a cell) would exacerbate an energy crisis and would be threatening for cell survival, whereas inhibition of the pump activity would be beneficial for overcoming the apoptotic insult (56). Interestingly, inhibition of Na,K-ATPase by ouabain is known to delay the development of apoptosis (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that cellular ATP levels are a determinant for apoptosis (Richter et al 1996), most likely through the Na 1 /K 1 ATPase (Wang et al 2003). Furthermore, insufficient Na 1 /K 1 ATPase activity to maintain ionic balances in response to episodes of ischemia, hypoglycemia, and epilepsy contributes to the neuropathy observed in those disorders (Lees 1991).…”
Section: Dts1mentioning
confidence: 99%